The Isolation and Purification Exception to the General Unpatentability of Products of Nature - Gipstein, Richard Seth (Science and Technology Law Review, 2002)
It is generally accepted that those discoveries which unambiguously claim a “product of nature” are not patentable. However, courts have failed to adequately define what, precisely, a “product of nature” is. The ambiguity seems to arise from the difficulty in determining where on the spectrum of human intervention a natural product, changed by human hands, ceases to be a natural product. This paper explores the isolation and purification exception to the products of nature doctrine, an exception first announced by Learned Hand in a 1911 case upholding a product patent on purified adrenaline. At the time that case was decided, there was an interesting but unspoken divergence in the line of cases dealing with purifications. One line dealt with purification of man-made products, finding the requisite novelty in the new use of the product. The other line of cases dealt with purified natural substances, where the only work of man was in the extraction and purification of the pre-existing and naturally-occurring materials. This second line of cases generally led to a denial of patent protection. Learned Hand, perhaps inadvertently, extended the logic of the first line of cases to the second, allowing purified adrenaline to receive patent protection and laying the foundation for what has become a “biotherapeutic” exception to the products of nature doctrine. This exception has not been extended to other areas of science. This paper argues that Hand’s insulated exception cannot be logically justified from either a formalistic or economic perspective.